Phase I/II Trial of Anticarcinoembryonic Antigen Radioimmunotherapy, Gemcitabine, and Hepatic Arterial Infusion of Fluorodeoxyuridine Postresection of Liver Metastasis for Colorectal Carcinoma - Cahan, Benjamin (Cancer Biother Radiopharm, 2017)
Objectives: Report the feasibility, toxicities, and long-term results of a Phase I/II trial of (90)Y-labeled anticarcinoembryonic antigen (anti-CEA) (cT84.66) radioimmunotherapy (RIT), gemcitabine, and hepatic arterial infusion (HAI) of fluorodeoxyuridine (FUdR) after maximal hepatic resection of metastatic colorectal cancer to the liver. Methods: Patients with metastatic colorectal cancer to the liver postresection or ablation to minimum disease were eligible. Each cohort received HAI of FUdR for 14 days on a dose escalation schedule. The maximum HAI FUdR dose level planned was 0.2 mg/kg/day, which is the standard dose for HAI FUdR alone. On day 9, (90)Y-cT84.66 anti-CEA at 16.6 mCi/m(2) as an i.v. bolus infusion and on days 9–11 i.v. gemcitabine at 105 mg/m(2) were given. Patients could receive up to three cycles every 6 weeks of protocol therapy. Four additional cycles of HAI FUdR were allowed after RIT. Results: Sixteen patients were treated on this study. A maximum tolerated dose of 0.20 mg/kg/day of HAI FUdR combined with RIT at 16.6 mCi/m(2) and gemcitabine at 105 mg/m(2) was achieved with only 1 patient experiencing grade 3 reversible toxicity (mucositis). After surgery, 10 patients had no evidence of visible disease and remained without evidence of disease after completion of protocol therapy. The remaining 6 patients demonstrated radiological visible disease after surgery and after protocol therapy 2 patients had a CR, 1 patient had PR, 2 had stable disease, and 1 had progression. With a median follow-up of 41.8 months (18.7–114.6), median progression free survival was 9.6 months. Two patients demonstrated long-term disease control out to 45+ and 113+ months. Conclusion: This study demonstrates the safety, feasibility, and potential utility of HAI FUdR, RIT, and systemic gemcitabine. The trimodality approach does not have higher hematologic toxicities than seen in prior RIT-alone studies. Future efforts evaluating RIT in colorectal cancer should integrate RIT with systemic and regional therapies in the minimal tumor burden setting.